Weighing factors responsible for the production of the Catalan vowel /ɛ/ versus /e/ contrast in three districts of Barcelona. (December 2019) - Cortés, Susana; Lleó, Conxita; Benet, Ariadna
Aims and objectives/purpose/research questions: This study investigates the sociolinguistic factors associated with the maintenance or loss of the mid-front vowel contrast in the Catalan spoken by Spanish-Catalan bilinguals in three districts of Barcelona. It addresses the following questions. (1) Is the mid-front vowel contrast kept in all the districts under study? Do we find differences across districts and/or age groups? (2) Is an auditory analysis of our data further supported by an acoustic analysis? (3) Which sociolinguistic factors help us predict whether the contrast is kept or lost? Design/methodology/approach: Participants in this study were 36 bilingual children and 36 bilingual adults who completed a picture-naming task. Participants lived in Gràcia/Eixample (two districts with a low degree of Spanish presence) or in Nou Barris (a district with a high degree of Spanish presence). Data and analysis: The production of words with target /ɛ/ and with target /e/ by each participant was recorded along with the answers to a sociolinguistic questionnaire. The spoken data were auditorily and acoustically analysed, and then statistically analysed in relation to different sociolinguistic factors that could account for the maintenance or loss of this vowel contrast. Findings/conclusions: Significant differences were found in the production of children across districts but not in that of adults. The children in Nou Barris show an advanced merger between /ɛ/ and /e/. The language in the environment seems to be the main factor, as the merger or maintenance of the contrast correlates with the language spoken by our participants' peer group and close relatives. Originality: This research combines both an auditory and acoustic analysis of phonological data with sociolinguistic information about speakers from different districts in Barcelona. Significance/implications: This paper contributes to a better understanding of phonological variation within Barcelona and the sociolinguistic factors that are responsible for variation among its population.